Th0-like CD4+ T cells protect mice with murine retrovirus-induced immunodeficiency syndrome (MAIDS) against co-infection with Listeria monocytogenes. - Hiromatsu, K (1996)
We examined the host defence mechanism against infection with Listeria monocytogenes, a facultative intracellular bacterium, in mice with murine acquired immunodeficiency syndrome (MAIDS) caused by LP-BM5 murine leukaemia virus (MuLv) infection. Although LP-BM5 MuLV infection in C57BL/6 mice leads to a stage of immunodeficiency characterized by severe compromise of cell-mediated immunity, the mice with established MAIDS infected with LP-BM5 8 weeks previously, showed resistance to an intraperitoneal infection with Listeria monocytogenes. These MAIDS mice also showed resistance to a lethal dose of secondary listerial challenge, while the delayed-type hypersensitivity response to heat-killed Listeria (HKL.) was severely impaired in MAIDS mice. The resistance of MAIDS mice to listerial infection was mediated by CD4+ alpha beta T cells but neither by gamma delta T cells nor natural killer (NK) cells. Interferon-gamma (IFN-gamma) and interleukin-10 (IL-10) were produced by CD4+ T cells from Listeria-infected MAIDS mice in response to the in vitro stimulation with HKL, whereas IFN-gamma but not IL-10 were produced by those from Listeria-infected control mice. These results suggest that T-helper 0 (Th0)-like immune responses of CD4+ T cells occur and participate in host defence mechanisms against listerial infection in MAIDS mice.